Effects of hypo- and hyperthermia, berberine and the combination of berberine with hyperthermia on osteosarcoma cells / Mohammed Ali Orba Nashirty - Nashirty, Mohammed Ali Orba (Institute of Graduate Studies, UiTM, 2018)
Osteosarcoma is the most common primary malignant bone tumour with a high resistance to chemo- and radiotherapy. Hyperthermia is a well-established type of cancer treatment. However, the molecular changes and responses of osteosarcoma cells to hyperthermia are not well understood. Hypothermia has been proven to be protective in certain medical situations such as brain surgery, but there is no published study about its effect in bone cancer. According to literature, about 60% of all cancer patients take supplements without informing their oncologists during therapy. Little is known about the effect of antioxidants like berberine chloride on osteosarcoma cells, especially in combination with hyperthermia. Berberine is a natural alkaloid available in several traditional herbs, and it can help treat many pathological conditions. The overall objective of this study is to investigate the short- and long-term effects of various stages of hyper- and hypothermia on osteoblastlike osteosarcoma cells and its underlying mechanism of action. It also seeks to study the long-term effect of a single short-term treatment with severe hyperthermia (45°C, 1 h) on osteosarcoma cells and its underlying causes. An additional objective is to investigate the effect of hyperthermia alone and in combination with berberine chloride on osteosarcoma cells and its underlying mechanisms. Osteoblast-like osteosarcoma cells (MG-63 cells) were treated with hyper- and hypothermia for short, medium and long-term periods. Some cells were also treated with berberine chloride and a combination of berberine chloride with mild, moderate, and severe hyperthermia. Severe hypothermia and hyperthermia showed a time-dependent toxicity; hence viability was reduced in a significant manner at all time points, whereas mild hypothermia showed a protective effect...